PARENTING CLASS: STUDI NARATIF PELIBATAN ORANGTUA PADA PENDIDIKAN ANAK USIA DINI DI KOTA BANJARMASIN - Nugerahani Ilise, Rizki; Azizah, Aspiya (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to explore parents' perceptions regarding the benefits, constraints, and expectations of the Parenting Class program in early childhood education in Banjarmasin City. Parenting Class is an educational program designed to improve parents' understanding of parenting patterns, child development, and effective educational strategies. This study uses a qualitative approach with a narrative study method, collecting data through in-depth interviews with parents who participated in the program. The results showed that Parenting Class provides many benefits, such as increasing parents' knowledge of parenting patterns that are appropriate to the child's developmental stage, and helping to strengthen the relationship between parents and children. This program also increases parental involvement in children's education at school. However, several constraints were found, such as limited time for working parents, difficulty attending scheduled sessions, and less flexible delivery methods. Some parents hoped for the option of online classes or recorded sessions to facilitate their participation.